TINGKAT KESIAPAN MEMASUKI DUNIA KERJA SISWA KELAS XII JURUSAN TEKNIK GAMBAR BANGUNAN DI SMK N 1 LEMBAH MELINTANG PASAMAN BARAT - 1082-1102 , Romadoni (CIVED, 2016)
ABSTRAKBased on the initial survey, the readiness of student to enter the working world, les for cognitive (knowledge), affective (attitude), and psychomotor (skills). This study aims to determine the level of readiness of students of class XII Architecture Engineering Departement at SMK N 1 valley crossing to enter the working world with regard to the readiness of the knowledge, readiness posture, and readiness skill.This research uses descriptive method. The research subjects are student of class XII Architecture Engineering Departement at SMK N 1 valley crossing semester of the school year 2015/2016. Cognitive data collection taken from the value of learning outcomes (report) while in class X and XI, the data using observation sheet affective, psychomotor using the data sheet psychomotor assessment work. The analysis techniques using quantitative descriptive analysis.These result indicate that grade students of class XII Architecture Engineering Departement at  SMK N 1 valley crossing in cognitive, affective, and psychomotor are in the category of ready to enter the working world.Keywords: Readiness, World of Work, Knowledge, Attitudes, Skill.